PENGARUH PENERAPAN PAJAK PENGHASILAN PP NO.46 TAHUN 2013 TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KOTA MADIUN - Prakoso, Fernandhi Dwi; Rustam, Akie Rusaktiva (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The government issued a new policy on income tax for MSMEs ie PP No.46 Year 2013. They hopes the new policy will make MSMEs more obedient to pay their tax and encourage other MSMEs become a tax payer. This research study tax compliance rate in Madiun City by using several variables which have been used in some previous research such as understanding income tax, tax rate, tax penalty, and tax payment service that focusing on PP No.46 Year 2013.Â The aims is to analyse the impact of four variabels independent on MSMEsâ€™s tax compliance. Result show that understanding of income tax, and tax payment service of PP No.46 Year 2013 have a significant impact toward MSMEsâ€™s tax compliance in Madiun City. Keywords: Tax compliance, MSMEs, PP No.46 Year 2013.